Data analysis : an introduction - Lewis-Beck, Michael S. (Thousand Oaks : Sage Publications, 1995)
This accessible introduction to data analysis focuses on the interpretation of statistical results, in particular those which come from nonexperimental social research. It will provide social science researchers with the tools necessary to select and evaluate statistical tests appropriate for their research question
Includes bibliographical references.
Keywords: Social sciences -- Statistical methods